Green Tea Consumer Preferences: Consumption Patterns and Influencing Factors in Banyumas Regency, Central Java - Muthia Auralia; Hega Bintang Pratama Putra; Rangga Wasi Hastrawirid (Diponegoro University, 2025)
Individuals consume green tea according to their needs and desires. Product evaluations reflect consumer preferences and influence consumer attitudes. The purpose of this study was to examine consumer characteristics, and identify factors influencing consumer preferences for green tea. The study location was Banyumas Regency, Central Java, from June to July 2025. This study used a survey method with a sample selected through multistage random sampling. Respondents consisted of 120 green tea consumers. Data analysis used descriptive analysis and principal component analysis (PCA). The results showed that most green tea consumers were women of various ages. Furthermore, married consumers purchased green tea to share with their families. Most consumers had a bachelor's degree and earned more than IDR 3,500,000. Regarding consumption habits, on average, individuals drank green tea once a day with breakfast. The average monthly consumption was 50 grams, which they shared with their families. Green tea was usually purchased once a month at supermarkets, with an average of 50 grams. Preference for green tea was shaped by three main factors: the value attached to tea (character), appearance (identity), and product image.